Differences in the Upper-Limb Coordination of Primary School Children - Miljan Hadzovic; Predrag Ilic; Aleksandra Aleksic Veljkovic (Lithuanian Sports University, 2020)
Background. Monitoring the abilities of typically developed children is very important. Methods. This study aimed to determine the levels and differences in motor coordination of the upper extremities between first and third-grade primary school children using the subtest of the Bruininks-Oseretsky Test (BOT-2). The sample included 79 healthy subjects of both sexes, chronological age ranging from seven to nine years, body height 134.51 ± 8.43 cm (Mean ± SD), bodyweight 33.01 ± 8.65 kg (Mean ± SD). The Mann-Whitney U test determined differences between groups, for the benefit of the group of third-grade subjects in all upper extremity coordination variables. Results. The results showed that differences in age and biological growth and development in young children in some variables of upper-limb coordination influenced medium size (2ULC, 6ULC, 7ULC), but in most of the variables examined they had great influence (1ULC. 3ULC, 4ULC, 5ULC, TULC) according to Cohen's criterion. Conclusion. It can be concluded that well-organized and expertly guided physical activities, as well as regular testing of children when it comes to developing coordination, can influence early detection of movement difficulties and eliminate problems in acquiring new coordination skills, and thus create an appropriate base for engaging in sports activities while growing up.  Keywords: motor development, coordination, physical education.